Modeling and Optimization of Phenolic Compounds Removal from Petrochemical Industry by Electrocoagulation: A Comparative study - Ehssan Mohamed Reda Nassef, Ahmed Osama Fathy Soliman, Nabil Abd El Monem, (Design Engineering, 2022)
The world has witnessed enormous rise in petrochemical industry due to its versatile applications. The wastewater discharged from petrochemical industry is origin of various contaminants that is hazardous to human and aquatic life. This study aims at implementing the statistical modeling as well as process optimization for treating phenol, major organic pollutant in petrochemical industry, through electrocoagulation for batch and continuous system. Aluminum (Al) was utilized as electrode material. Central composite design was used to design and optimize the process conditions. The key parameters include [Phenol]in, Flow rate, Current Density and Operating time were used to study their effects on Residual Concentration and %Removal. After analyzing the fit summary generated by RSM, it has been observed that quadratic model is most suitable whereas parametric evaluation exhibited that [Phenol]in impart most significant contribution in linear and interactive effect. Moreover, 63.25% of phenol was removed and 9.7 mg/L of residual concentration was achieved under optimum values of parameters (Time= 74.59 min; Current Density; 2.5 mA/cm2; [Phenol]in = 26.4 mg/L) in batch experiments whereas 73.8% of %Removal was accomplished along with 1.31 mg/L of residual concentration in continuous conditions under optimum operational parameters (Time= 85.52 min; Flow Rate =3.5 L/min ; [Phenol]in = 5.003 mg/L).